Conventional bank and islamic banking as institutions: Similarities and differences - Wan Hakimah, Wan Ibrahim; Abdul Ghafar, Ismail (Emerald Group Publishing Ltd., 2015)
Purpose The aim of this paper is to discuss the similarities and differences of both conventional and Islamic financial institutions from various institutional perspectives.